A 54 Gy in three fractions of stereotactic body radiotherapy using CyberKnife for T1b-2aN0M0 pathologically confirmed non-small cell lung cancer. (27th September 2021) - Abe, Takanori; Ryuno, Yasuhiro; Iino, Misaki; Saito, Satoshi; Aoshika, Tomomi; Ohta, Tomohiro; Igari, Mitsunobu; Hirai, Ryuta; Kumazaki, Yu; Kaira, Kyoichi; Kagamu, Hiroshi; Ishida, Hironori; et al.
Abstract: Objective: Optimal dose-fractionation regimen of stereotactic body radiotherapy for peripheral early-stage non-small cell lung cancer remains unclear. We retrospectively investigated outcomes of stereotactic body radiotherapy using CyberKnife at 54 Gy in three fractions in 26 patients (median age: 76 years) with pathologically confirmed T1b–T2aN0M0 non-small cell lung cancer. Methods: A 54 Gy in three fractions was prescribed to cover the 99% of gross tumor volume. We estimated cumulative local control, progression-free survival and overall survival rates (Kaplan–Meier method), and toxicity (Common Toxicity Criteria for Adverse Events, version 5.0). Results: All the tumors were located at peripheral area of lung. Mean distance from chest wall to tumor was 6.5 mm (range: 0–32 mm). The patients' pathological diagnoses were: adenocarcinoma: n = 18, squamous cell carcinoma: n = 7 and non-small cell carcinoma: n = 1. Their stages were T1b: n = 9, T1c: n = 14 and T2a: n = 3. Median follow-up was 24 months (range: 6–54). Cumulative 2-year effect rates were local control: 100%, progression-free survival 70% and overall survival: 92%. Twenty patients developed grade one radiation pneumonitis, but grade 2 or greater radiation pneumonitis was not observed. Conclusions: We found CyberKnife-stereotactic body radiotherapy for pathologically confirmed T1b–T2aN0M0 non-small cell lung cancer to be effective and safe. However, these results should be validated with a larger patient cohort and prospective follow-up monitoring. Abstract : A 2-year local control and overall survival were 100 and 92% without any severe lung toxicity after 54 Gy in three fractions of stereotactic body radiotherapy for early-stage lung cancer.